2008
DOI: 10.1529/biophysj.107.122788
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Membrane Proteins by Dietary Lipids: Effects of Cholesterol and Docosahexaenoic Acid Acyl Chain-Containing Phospholipids on Rhodopsin Stability and Function

Abstract: Purified bovine rhodopsin was reconstituted into vesicles consisting of 1-stearoyl-2-oleoyl phosphatidylcholine or 1-stearoyl-2-docosahexaenoyl phosphatidylcholine with and without 30 mol % cholesterol. Rhodopsin stability was examined using differential scanning calorimetry (DSC). The thermal unfolding transition temperature (T(m)) of rhodopsin was scan rate-dependent, demonstrating the presence of a rate-limited component of denaturation. The activation energy of this kinetically controlled process (E(a)) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 65 publications
0
33
1
Order By: Relevance
“…We suggest that DHA could also modify protein conformation, although we did not find a change in conformation with MHC class I. Nevertheless, a series of experimental studies by several laboratories have shown that DHA can modify the conformation of the G protein-coupled receptor rhodopsin by binding into the grooves between specific helices (39)(40)(41)(42).…”
Section: Discussioncontrasting
confidence: 54%
“…We suggest that DHA could also modify protein conformation, although we did not find a change in conformation with MHC class I. Nevertheless, a series of experimental studies by several laboratories have shown that DHA can modify the conformation of the G protein-coupled receptor rhodopsin by binding into the grooves between specific helices (39)(40)(41)(42).…”
Section: Discussioncontrasting
confidence: 54%
“…Docosahexaenoic acid is essential to the structure and function of photoreceptor cells in both the retina and the pineal organ (43)(44)(45)(46). Accordingly, VT-AANAT might have functioned to enhance the efficiency of the primitive vertebrate's photodetector by preventing arylalkylamine adduct formation with several essential photodetection molecules.…”
Section: Discussionmentioning
confidence: 99%
“…(58) More recently, the concentration of cholesterol and docosahexaenoic acid (DHA) containing lipids have been shown specifically to affect the properties of rhodopsin from retinal rod cells. (31) In this recent study, rhodopsin reconstituted into artificial lipid assemblies, containing varying concentrations of these two biomolecules, exhibited changes in its denaturation temperature dependent upon the bilayer composition. Increased cholesterol appeared to stabilize the protein.…”
Section: Resultsmentioning
confidence: 90%
“…Membranes containing both cholesterol and the poly-unsaturated docosahexaenoic acid containing lipids have been shown to impact the stability of embedded rhodopsin molecules. (31) Additionally, phenotypes that are deficient in polyunsaturated acids and cholesterol have been linked to visual disfunction. (32) (22) Given the importance of these species in regulating rhodopsin, increased understanding of the distribution of these lipids in intact cells may provide further insight into role of lipid environments that regulate protein function.…”
Section: Introductionmentioning
confidence: 99%